EFFECTS OF CORPORATE GOVERNANCE ON LOAN PERFORMANCE OF COMMERCIAL BANKS IN KENYA - MAGEMBE, MORAGWA J. (My University, 2017)
The study examined the Corporate Governance variables and Loan Performance of commercial banks in Kenya. The study aimed at establishing the effects of corporate governance variables (BS, AS and CEO duality) on Loan Performance of commercial banks in Kenya. Descriptive research design was used in this study. The population involved in this study was all the 43 commercial banks in Kenya. A sample of 43 commercial banks was used to obtain sample representation of the entire population this is because the sample size is manageable. Both Primary and secondary data were obtained by administering questionnaires to the CEOs of the banks and also informational data was obtained from the published annual reports and company sources spanning five years (2010-2014). Karlpearsons Correlation Coefficient and Multiple Regression Analysis were used to determine the magnitude of the relationship between corporate governance variables and loan performance. Stata version 13 program was also used in analyzing the data. The BS has a positive relation on the loan performance levels of the commercial banks meaning that bigger boards, lower frequency of the board meetings and less number of independent directors tend to reduce the level of the lNPLs hence leading to better loan performance levels for the banks however this was not significant for this study. AS has a significantly negative relation on the loan performance levels in that; as the AS increases, it reduces the lNPLs also higher frequency of the meetings and the increase in the number of independent auditors reduces the lNPLs leading to better loan performance. CEO duality shows a positive relation to the lNPLs in that the separation of the CEOs office and that of the chair leads to a decrease of the lNPLs thus resulting to better loan performance. From the R square value of the regression test findings, corporate governance factors (BS, AS and CD) account for 86% of the loan performance of commercial banks. The study then recommends that the banks need to avoid overloaded agenda in their committees and rather emphasis on the quality of the agenda. More efforts also need to be employed at increasing the year size, looking at other corporate governance variables like; board expertise, policy formulation and implementation and board tenure not forgetting the use of other financial performance measures like ROE and ROA.
Keywords: Corporate Governance